Stem-focused green service learning: Enhancing interactive learning and sustainability with INAQ - Mohd Hafiz Abu Hassan; Ts. Dr. Hatika Kaco; Khairunneezam Mohd Noor; Najwa Hayaati Mohd Alwi; Siti Salhah Othman; Siti Nazurah Md Jusoh; Nur Amirah Zulaikha Muzaffar (Universiti Sains Islam Malaysia, 2025)
‘Abqari Journal. Volume 32, Issue 2 Page (119–129)